The imitative mind : (Cambridge University Press, 2002)
Modern research demonstrates that imitation is more complex and interesting than classical theories proposed. Monkeys do not imitate whereas humans are prolific imitators. This book provides an analysis of empirical work on imitation and shows how much can be learned through interdisciplinary research ranging from cells to individuals, apes to men, and babies to adults. Covering diverse perspectives on a great puzzle of human psychology, the book is multidisciplinary in its approach to revealing how and why we imitate.